2020
DOI: 10.21203/rs.3.rs-60477/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Combination of Trehalose and Glycerol: An Effective and Non-Toxic Recipe for Cryopreservation of Human Adipose-Derived Stem Cells

Abstract: Background: Adipose-derived stem cells (ADSCs) promote tissue regeneration and repair. Cryoprotective agents (CPAs) protect cells from cryodamage during cryopreservation. Safe and efficient cryopreservation of ADSCs is critical for cell-based therapy in clinical applications. However, most CPAs are used at toxic concentrations, limiting their clinical application. Objective: The aim of this study is to develop a non-toxic xeno-free novel CPA aiming at achieving high-efficiency and low-risk ADSC cryopreservatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Several studies have reported that using DMSO or DMSO + FBS as CPAs was effective in protecting adipose tissue cell survival and retention of the adipose tissue volume compared with the absence of CPA 9,[21][22][23][24] . However, the use of DMSO and FBS has the risk of toxicity and zoonotic infection 25 . When these agents are applied in tissue cryopreservation, especially in adipose tissue that is grafted into the human body in a large volume, toxicity may become a major concern [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that using DMSO or DMSO + FBS as CPAs was effective in protecting adipose tissue cell survival and retention of the adipose tissue volume compared with the absence of CPA 9,[21][22][23][24] . However, the use of DMSO and FBS has the risk of toxicity and zoonotic infection 25 . When these agents are applied in tissue cryopreservation, especially in adipose tissue that is grafted into the human body in a large volume, toxicity may become a major concern [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%